2020
DOI: 10.1177/0300060520939695
|View full text |Cite
|
Sign up to set email alerts
|

Association between fish intake and glioma risk: a systematic review and meta-analysis

Abstract: Objectives We investigated the association between the consumption of fresh and processed fish and glioma risk using a meta-analysis approach. Methods We selected and analyzed observational studies that discussed the relationships between fresh and processed fish intake on glioma risk from PubMed, Web of Science, Embase, and the SinoMed and Wanfang databases from inception to 31 March 2020. Studies were selected according to pre-established eligibility criteria and data were extracted separately by two researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…For example, a previous metaanalysis of eight observational studies, reporting the association between dietary fresh fish and processed fish intake and the risk of glioma, revealed that higher intake of fresh fish could significantly reduce the risk of glioma (RR = 0.823, 95% CI: 0.698-0.970) (68). Significant inverse association was also found in another meta-analysis by Lei et al (56). Lei et al's study found that compared with the lowest category, the highest category of fresh fish intake was significantly associated with a reduced risk of glioma (OR = 0.72; 95% CI: 0.53-0.97; P = 0.032).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…For example, a previous metaanalysis of eight observational studies, reporting the association between dietary fresh fish and processed fish intake and the risk of glioma, revealed that higher intake of fresh fish could significantly reduce the risk of glioma (RR = 0.823, 95% CI: 0.698-0.970) (68). Significant inverse association was also found in another meta-analysis by Lei et al (56). Lei et al's study found that compared with the lowest category, the highest category of fresh fish intake was significantly associated with a reduced risk of glioma (OR = 0.72; 95% CI: 0.53-0.97; P = 0.032).…”
Section: Discussionmentioning
confidence: 82%
“…Experimental studies have shown that above these compounds result in cell cycle arrest, and promote anti-tumor efficacies of lomustine in glioblastoma cells ( 54 , 55 ). A recent meta-analysis examining the association of fish intake with glioma also concluded that higher consumption of fresh fish was associated with a reduced risk of glioma ( 56 ). Finally, vegetables, fruits and whole grains also contain large amounts of dietary fiber.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between fish consumption and mortality is presented in Table 1 (19)(20)(21)(22)(23)(24)(25)(26)(27). Table 2 (14,22,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) presents the associations between consumption of fish and cancer outcomes (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), while those between fish consumption and CVD are presented Table…”
Section: Characteristics Of Meta-analysesmentioning
confidence: 99%